Eksistensi Industri Musik Korea (K-Pop) pada Perubahan Gaya Berkomunikasi dan Perilaku Konsumtif K-Popers di Surabaya - Rohima , Qonitatul Mustafidha; Aini, Devi Nur; Setyarahajoe, Ratna (Kinesik, 2024)
The K-pop phenomenon has become one of the major forces in the global music industry. Not only trending in South Korea, K-pop has taken the international stage with a large and diverse fan base around the world. However, the appeal of K-pop is not only limited to the music aspect; this phenomenon also affects various aspects of teenagers' lives, including their communication style and consumptive behavior. This study aims to determine the communication style and consumptive behavior of fashion innovation kpopers in Surabaya. This research uses a qualitative approach by spreading google forms on social media, such as WhatsApp, Instagram, and Twitter. The results of this study show that the existence of K-Pop has changed communication patterns between fans and expanded interactions through social media. In addition, the K-Pop industry also encourages consumptive behavior among fans with increased interest in Korean pop culture merchandise (fashion).